Favorable surgical treatment outcomes for chronic constipation with features of colonic pseudo-obstruction - Han, Eon Chul (Baishideng Publishing Group Co., Limited, 2012)
AIM: To determine long-term outcomes of surgical treatments for patients with constipation and features of colonic pseudo-obstruction. METHODS: Consecutive 42 patients who underwent surgery for chronic constipation within the last 13 years were prospectively collected. We identified a subgroup with colonic pseudo-obstruction (CPO) features, with dilatation of the colon proximal to the narrowed transitional zone, in contrast to typical slow-transit constipation (STC), without any dilated colonic segments. The outcomes of surgical treatments for chronic constipation with features of CPO were analyzed and compared with outcomes for STC. RESULTS: Of the 42 patients who underwent surgery for constipation, 33 patients had CPO with dilatation of the colon proximal to the narrowed transitional zone. There were 16 males and 17 females with a mean age of 51.2 ± 16.1 years. All had symptoms of chronic intestinal obstruction, including abdominal distension, pain, nausea, or vomiting, and the mean duration of symptoms was 67 mo (range: 6-252 mo). Preoperative defecation frequency was 1.5 ± 0.6 times/wk (range: 1-2 times/wk). Thirty-two patients underwent total colectomy, and one patient underwent diverting transverse colostomy. There was no surgery-related mortality. Postoperative histologic examination showed hypoganglionosis or agangliosis in 23 patients and hypoganglionosis combined with visceral neuropathy or myopathy in 10 patients. In contrast, histology of STC group revealed intestinal neuronal dysplasia type B (n = 6) and visceral myopathy (n = 3). Early postoperative complications developed in six patients with CPO; wound infection (n = 3), paralytic ileus (n = 2), and intraabdominal abscess (n = 1). Defecation frequencies 3 mo after surgery improved to 4.2 ± 3.2 times/d (range: 1-15 times/d). Long-term follow-up (median: 39.7 mo) was available in 32 patients; all patients had improvements in constipation symptoms, but two patients needed intermittent medication for management of diarrhea. All 32 patients had distinct improvements in constipation symptoms (with a mean bowel frequency of 3.3 ± 1.3 times/d), social activities, and body mass index (20.5 kg/m(2) to 22.1 kg/m(2)) and were satisfied with the results of their surgical treatment. In comparison with nine patients who underwent colectomy for STC without colon dilatation, those in the CPO group had a lower incidence of small bowel obstructions (0% vs 55.6%, P < 0.01) and less difficulty with long-distance travel (6.7% vs 66.7%, P = 0.007) on long-term follow-up. CONCLUSION: Chronic constipation patients with features of CPO caused by narrowed transitional zone in the left colon had favorable outcomes after total colectomy.